The use of a lower-limb prosthetic device to improve performance factors in elite paracanoe - Rebensburg, A. J.; Boettcher, A. E.; Perrin, O. D.; Rettke, D. J.; Hawke, A. L.; Breen, S. (ISBS Proceedings Archive (Michigan), 2019)
The current study examined how a lower-limb prosthesis affected paracanoe performance factors. One paracanoe athlete completed two, 30 second tethered sprints with and without the use of a custom prosthesis. Kinematic and kinetic performance variables were compared. When the prosthesis was worn, a significant increase in propulsion impulse was observed on the right side (50 Ns to 61 Ns), which may have been due to enhanced contact between the residual limb and the kayak. Stroke rate symmetry index became significantly more symmetrical while wearing the prosthesis (0.27 to 0.01); perhaps due to a more upright trunk position, decreasing variability in center of gravity movement. In conclusion, based on the results, the addition of a prosthesis for the paracanoe athlete in the present study had a positive effect on performance factors.